SOME ENERGETIC PROPERTIES OF MINERAL ASSEMBLAGES - Rakhov E.V. (My University, 2006)
The energetic aspects of redistribution of chemical bonds of lithospheric material during metamorphism, metasomatism, and hydrothermal activity attract interest in connection with the behavior of chemical elements (concentration and dispersion) in PT-gradient fields and the individual properties of atoms. The main function (isobaric–isothermal potential) used to study the phase relations in heterogeneous systems does not make it possible to analyze the transformation of chemical bonds during the change of mineral assemblages in rocks initiated by variation of intense parameters.